CAPITALISTAS, CACIQUES Y REVOLUCION: LA FAMILIA TERRAZAS DE CHIHUAHUA, 1854-1911 - Wasserman, Mark (1988)
TRADUCCION DE: CAPITALISTS, CACIQUES AND REVOLUTION. THE NATIVE ELITE AND FOREIGN ENTERPRISE IN CHIHUAHUA, MEXICO, 1854-1911